2021
DOI: 10.5267/j.ac.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of budget participation in improving managerial performance

Abstract: This study aims to analyze the effect of budget participation on the performance of the government apparatus of Palu City through budgetary slack with Culture kaili “Nosarara Nosabatutu” as moderating. This research was conducted in the regional apparatus organization of the Palu City Government in 41 regional work unit. Data were analyzed using Structural Equation Modeling with WARP PLS 7.0. The results show that budget participation has a positive effect on the performance of government officials, budget par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…This inconsistency greatly hinders the implementation and success of participative budget management (Figure 1). Budgetary participation, like any other decision taken in a participative way, has been shown to positively affect both the individual and the entire company (Amir et al, 2021;Hofstede, 1967;Kahar et al, 2016). It would be relevant for Tunisian companies to adopt and promote participative budgeting management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inconsistency greatly hinders the implementation and success of participative budget management (Figure 1). Budgetary participation, like any other decision taken in a participative way, has been shown to positively affect both the individual and the entire company (Amir et al, 2021;Hofstede, 1967;Kahar et al, 2016). It would be relevant for Tunisian companies to adopt and promote participative budgeting management.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, budgetary participation has attracted increasing attention (e.g., Amir et al, 2021;Apriwandi & Supriyono, 2021;Baccouri & Fedhila, 2017;Brownell, 1981;Brownell & Dunk, 1991;Kren, 1992;Lau et al, 2018;Lleo et al, 2020;Santos et al, 2021;Sofyani et al, 2020). Budgetary participation is defined as a process by which a manager is involved with, and has influence on, the determination of his or her budget (Shields & Shields, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the data was processed using WarpPLS Version 0.7. The stages of data analysis in PLS are [29] by developing a specification model, namely the path analysis model, including test the Measurement Model (Outer model) which is used to test the validity and test the reliability, structural Model Test (Inner model) to assess the effect of one variable on other variables, and weight estimation where the case value of the latent variable can be estimated. It is also done by evaluating the measurement model, structural models, and hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…Budgeting is one of the means to participate in decision-making. High budget participation can reduce budgetary slack (Amir et al, 2020;Rahman & Yixuan Ying, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research on budgetary slack has been widely studied, but there are still inconsistent results, for example, (Lakasse et al, 2021;Nurcahyono et al, 2021;Nurhikmat et al, 2016). found that the more people who participate in preparing the budget, the greater the opportunity creating budgetary slack but not with the study of (Amir et al, 2020;Maryati & Hendrawan, 2020). High asymmetry is an opportunity for management to create budgetary slack (.…”
Section: Introductionmentioning
confidence: 99%